Netizen Commentary Analysis on @nona_baygon Content: A Pro and Contra Study - Nurul Amalia; Salsabila Ibrahim (Sadida Islamic Communications and Media Studies, 2026)
This study aims to qualitatively describe netizen comments on the social media account @nona_baygon, focusing on the dynamics of pro and contra responses in digital spaces. A qualitative descriptive approach was applied using content analysis of comments on selected viral posts with high engagement levels. Data were collected through observation and documentation of user comments on social media platforms and analyzed through data reduction, categorization, and thematic interpretation based on positive, negative, and neutral sentiment tendencies. The findings indicate that netizen comments are dominated by emotional reactions divided into two main poles: support for the creativity of the content, which is considered unique, and criticism of its controversial style of delivery that often triggers public debate. This phenomenon shows that social media functions not only as a space for entertainment but also as a field for constructing social meaning, identity, and public opinion. The interaction reflects how societal perceptions are rapidly shaped within open and dynamic digital environments. The study concludes that @nona_baygon’s content has strong appeal that significantly generates public opinion polarization within modern social media ecosystems.